Creativity and Innovation 4.0. Fostering Renewal Through Possibility Thinking - Mangion, Margaret (Farol, 2024)
This paper explores the connections between creativity, innovation, and modern citizenship, focusing on "Creativity and Innovation 4.0" to understand how these dimensions contribute to technological advancements and reshape societal norms. The paper also addresses the challenges and limitations of possibility thinking, including technological inequalities. Ultimately, it outlines a pathway toward a society where creativity and innovation serve not only economic development but also the enrichment of democratic life.